Numerical analysis and experimental study of an ocean wave tetrahedral triboelectric nanogenerator. (1st February 2022) - Wang, Anqun; Chen, Jun; Wang, Li; Han, Junlei; Su, Weiguang; Li, Anqing; Liu, Pengbo; Duan, Liya; Xu, Chonghai; Zeng, Zheng
Highlights: A tetrahedral contact-separation nanogenerator was proposed for energy harvesting. The structure of the nanogenerator (the side length ratio and posture) was optimized. A thermohygrograph sensor node was self-powered by the proposed nanogenerator. Abstract: Ocean wave energy is increasingly regarded as promising blue energy for large-scale applications. Due to the low-frequency profile of the ocean wave energy, Triboelectric Nanogenerator provides an efficient harvesting way and convert into electrical energy. Contact area is an important factor for improving the output performance of triboelectric nanogenerators. However, in the popular structures (like nested rolling-spheres) of triboelectric nanogenerator, the contact area is small due to the point contact mode, which limits the energy harvest efficiency. In this paper, a contact-separation triboelectric nanogenerator based on a tetrahedron structure was designed and tested. The structure contains a smaller tetrahedron suspending inside a larger tetrahedron. Two regular tetrahedrons would contact and separate in the face-face mode when the structure is excited by external oscillation. The first order oscillation frequency of the structure is designed to match the major frequency of the ocean wave.The side length ratio between the internal and external regular tetrahedrons, and the posture of the structure were optimized to improve the power output. Experimental data showed that peak-to-peak voltage output and short-circuit current were at up to 200 V and 30 μA, respectively. Meanwhile, the peak power output reached 14.7 mW with 10 MΩ resistive load. The proposed TENG was able to light up to twenty commonly-used LED lamps (working voltage 3.0–3.4 V). A general thermohygrograph was succesfully powered by the proposed structure. This novel design coule be potentially used in the applications like the self-powered sensor node in the ocean by harvesting the free water wave energy.